Urban Corners in Guangzhou: Desing, Morphology and Everyday Life, 1757–1949 - Deng Hao; Chen Fei (Lodz University of Technology Press, 2023)
Urban corners are a distinct form of public space, yet little has been written about how this type of space has emerged and developed from a historical perspective. Addressing this gap, this paper presents a historical study of the spatial forms of urban corners in China. We reframe the Everyday Urbanism paradigm as an analytical framework to investigate the dynamics of the corners through three particular dimensions: design governance, morphological characteristics and everyday use. Drawing on historical sources such as maps, planning documents, old photographs and drawings, private written records and existing studies, we apply the framework to examine the transformation process of urban corners in the historic city core, Guangzhou, from 1757 to 1949. Findings suggest that urban corners have the potential to become an important cultural heritage in China’s historic cities. It concludes by discussing the implications of these findings for culture-led regeneration in contemporary China.
Keywords: urban corners; everyday urbanism; design governance; urban morphology; Guangzhou; zakątki miast; urbanistyka codzienna; zarządzanie projektowaniem; morfologia miast